Comparison of the light-sensitive and cyclic GMP-sensitive conductances of the rod photoreceptor: noise characteristics - Matthews, G (J Neurosci, 1986)
Patch-clamp recordings were made from outer segments of single rod photoreceptors isolated from toad retina. Cyclic GMP (cGMP) and its hydrolysis-resistant analog, 8-bromo-cGMP, increased the conductance of excised membrane patches when applied to the intracellular face of the membrane but not when applied to the extracellular face. The rectification properties of the cGMP-dependent conductance depended on the concentration of divalent cations bathing the intra- and extracellular membrane faces. Current flow was favored from the side of the membrane, either internal or external, that was exposed to bathing fluid free of divalent cations. The power spectral density of cGMP- induced noise was fitted by a sum of 2 Lorentzian components, with corner frequencies differing approximately 15-fold on average. This suggests that channel gating is controlled by 2 kinetic components. To compare the cGMP-sensitive conductance with the light-sensitive conductance of the rod, cell-attached patch-clamp recordings were made from intact, dark-adapted rods, and noise arising from the light- sensitive conductance was analyzed. The power spectrum of the light- sensitive noise also exhibited 2 Lorentzian components similar to those of the cGMP-sensitive conductance in excised patches. These results are consistent with the idea that cGMP opens the light-sensitive channel of the rod outer segment.